(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Driven by the continuous expansions of software applications and the increases in component varieties and sizes, the so-called component mismatch problem has become a more severe hurdle for component selection and integration. Although many component repositories and search tools have been proposed, so far there is no satisfactory solution which simultaneously achieves the following goals: automated, semantic-based, and precise. This paper presents a novel component repository and associated search tool which implements holistic semantic-based and adaptation-aware component specification and retrieval. The repository and tool is based on a Multiple-View and Interrelated Component Specification ontology model (MVICS), which has a smooth integration with domain related software system ontologies. The MVICS provides a formally defined and ontology-based architecture to specify components automatically in a spectrum of perspectives. The integration enhances the function and application scope of the MVICS model by bringing domain semantics into component specification and retrieval. The repository and search tool contributes to the current state of the art with four unique features: ontology-based component specification mechanism, semantic-based component retrieval method, adaptive component matching, and a comprehensive result component profile. The repository and tool has been widely tested and evaluated via its online version and follow-on survey reports, which concluded that they are effective for avoiding the component mismatch problem and is promising for industrial use.